ANALYSIS OF E-COMMERCE ADOPTION BY MSME IN FASHION SECTOR IN BANDUNG USING THE UTAUT MODEL - Mizal, Oldsie Meizilya; Wijayangka, Chandra (2020)
This research is motivated by the low level of adoption of E-commerce by MSMEs in the city of Bandung. Based on the pre-survey, there are difficulties faced by SMEs in adopting e-commerce, one of which is the lack of available facilities. The Fashion sector, as the sector that has shown the most significant growth in Bandung, is considered appropriate to be the object of this research. This study aims to determine the factors of technology adoption that are obstacles to SMEs in adopting E-commerce. This research uses quantitative methods as the type of descriptive research. The sampling technique uses nonprobability sampling technique with 200 respondents. Data analysis techniques using descriptive analysis and SEM-PLS path analysis. The independent variable in this study is Performance Expectancy, Effort Expectancy, Social Expectancy and Facilitating Condition. The dependent variable is Use Behavior and the intervening variable is Behavioral Intention. Based on descriptive analysis, E-commerce adoption using UTAUT shows high results, but there are low results on the Effort Expectancy and Social Influence variables which indicate that MSME actors still find difficulties in using E-commerce. The results obtained in this study are the Performance Expectancy, Effort Expectancy, and Social Expectancy variables that have a significant positive effect on Behavioral Intention. Meanwhile Behavioral Intention and Facilitating Conditions also have a significant positive effect on Use Behavior